2020
DOI: 10.3390/su12052102
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Control of Grain Purchase Price Affect the Sustainability of the National Grain Industry? One Empirical Study from China

Abstract: As one of the most important grain protection policies in China, the minimum purchase price policy prevents the fluctuation of grain output and protects the interests of farmers by regulating the prices of major grain varieties. For developing countries with a shortage of agricultural resources, represented by China, an in-depth study on the implementation effect and public satisfaction of this policy is of great significance for promoting the sustainable development of the grain industry. Based on the interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Concurrent socio-economic upheavals, like the economic crises of 2008, resulting in urban unemployment, prompted a rural return [101,102], aligning with the observed increase in recultivation area during this period (Figure 13c). Additionally, region-specific agricultural strategies, such as the minimum purchase price for grain products in provinces like Jiangxi, Anhui, and Jiangsu, contributed to the post-2009 surge in recultivation [103,104].…”
Section: Cropland Abandonment and Recultivation Driversmentioning
confidence: 99%
“…Concurrent socio-economic upheavals, like the economic crises of 2008, resulting in urban unemployment, prompted a rural return [101,102], aligning with the observed increase in recultivation area during this period (Figure 13c). Additionally, region-specific agricultural strategies, such as the minimum purchase price for grain products in provinces like Jiangxi, Anhui, and Jiangsu, contributed to the post-2009 surge in recultivation [103,104].…”
Section: Cropland Abandonment and Recultivation Driversmentioning
confidence: 99%
“…The amount of rice and corn planted has significantly increased as a result of the minimum purchase price for crops, the cost of temporary storage, and the high demand for livestock products [60,61]. A previous study found that the minimum purchase price is a key factor in the northeast of China, Jiangxi province, Anhui province, and Jiangsu province, which may extend the positive contribution of yields in these regions, and therefore, outweigh other factors [62].…”
Section: Impact Of Agricultural and Land Management Practicesmentioning
confidence: 99%
“…Since the beginning of the 21 st century, China's agricultural subsidy policy has continuously been reformed to regulate crop prices (Lopez et al 2017). In 2008, TPP was implemented to stabilise agricultural product prices and increase crop production (Liu et al 2020a). However, continuous increases in grain production have seriously distorted the market mechanism of agricultural products, thus intensifying the imbalance between the supply and demand of agricultural products in the domestic market (Li et al 2020).…”
mentioning
confidence: 99%